Kepatuhan Penumpang PT. Lion Air Rute Jakarta Batam Terhadap Peraturan Penerbangan - Lukiana Lukiana (Research and Development Agency of The Ministry of Transportation, 2010)
Air transportation is the most strategic means of transportation other than transportation, in terms of travel time and the distance. As we know at this the point the aircraft was affordable rates by the various layers of society, so that the consisted of various group both upper and lower levels of educational backgrounds very in which not all know and obey the rules / regulations for passenger aircraft well before the flight or during the flight. The purpose of this study is to determine the level of compliance with the regulations of passenger safety, especially in the aircraft. Results showed passenger planes in general have been largely understood and abide by the rules and restrictions that apply in supporting of flight safety.